Effect of Alirocumab Added to High-Intensity Statin Therapy on Coronary Atherosclerosis in Patients With Acute Myocardial Infarction: The PACMAN-AMI Randomized Clinical Trial - Räber, Lorenz; Ueki, Yasushi; Otsuka, Tatsuhiko; Losdat, Sylvain; Häner, Jonas D; Lonborg, Jacob; Fahrni, Gregor; Iglesias, Juan F; van Geuns, Robert-Jan; Ondracek, Anna S; Radu Juul Jensen, Maria D; Zanchin, Christian; et al. (JAMA : the journal of the American Medical Association, 2022)
Coronary plaques that are prone to rupture and cause adverse cardiac events are characterized by large plaque burden, large lipid content, and thin fibrous caps. Statins can halt the progression of coronary atherosclerosis; however, the effect of the proprotein convertase subtilisin kexin type 9 inhibitor alirocumab added to statin therapy on plaque burden and composition remains largely unknown. To determine the effects of alirocumab on coronary atherosclerosis using serial multimodality intracoronary imaging in patients with acute myocardial infarction. The PACMAN-AMI double-blind, placebo-controlled, randomized clinical trial (enrollment: May 9, 2017, through October 7, 2020; final follow-up: October 13, 2021) enrolled 300 patients undergoing percutaneous coronary intervention for acute myocardial infarction at 9 academic European hospitals. Patients were randomized to receive biweekly subcutaneous alirocumab (150 mg; n = 148) or placebo (n = 152), initiated less than 24 hours after urgent percutaneous coronary intervention of the culprit lesion, for 52 weeks in addition to high-intensity statin therapy (rosuvastatin, 20 mg). Intravascular ultrasonography (IVUS), near-infrared spectroscopy, and optical coherence tomography were serially performed in the 2 non-infarct-related coronary arteries at baseline and after 52 weeks. The primary efficacy end point was the change in IVUS-derived percent atheroma volume from baseline to week 52. Two powered secondary end points were changes in near-infrared spectroscopy-derived maximum lipid core burden index within 4 mm (higher values indicating greater lipid content) and optical coherence tomography-derived minimal fibrous cap thickness (smaller values indicating thin-capped, vulnerable plaques) from baseline to week 52. Among 300 randomized patients (mean [SD] age, 58.5 [9.7] years; 56 [18.7%] women; mean [SD] low-density lipoprotein cholesterol level, 152.4 [33.8] mg/dL), 265 (88.3%) underwent serial IVUS imaging in 537 arteries. At 52 weeks, mean change in percent atheroma volume was -2.13% with alirocumab vs -0.92% with placebo (difference, -1.21% [95% CI, -1.78% to -0.65%], P < .001). Mean change in maximum lipid core burden index within 4 mm was -79.42 with alirocumab vs -37.60 with placebo (difference, -41.24 [95% CI, -70.71 to -11.77]; P = .006). Mean change in minimal fibrous cap thickness was 62.67 μm with alirocumab vs 33.19 μm with placebo (difference, 29.65 μm [95% CI, 11.75-47.55]; P = .001). Adverse events occurred in 70.7% of patients treated with alirocumab vs 72.8% of patients receiving placebo. Among patients with acute myocardial infarction, the addition of subcutaneous biweekly alirocumab, compared with placebo, to high-intensity statin therapy resulted in significantly greater coronary plaque regression in non-infarct-related arteries after 52 weeks. Further research is needed to understand whether alirocumab improves clinical outcomes in this population. ClinicalTrials.gov Identifier: NCT03067844.